FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISKEUDES DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN DANA DESA - Anak Agung Ayu Erna Trisnadewi; Anak Agung Bagus Amlayasa; I-Wayan Rupa (Jurnal Akuntansi, 2020)
This study aims to determine the factors that influence the performance of SISKEUDES in improving the quality of the Village Fund's financial statements. Village financial management has become very important as part of the accountability of village funds given by the government and is increasing every year. The SISKEUDES application is used to facilitate the administration of village fund financial reports. The application of the SISKEUDES application will accelerate the completion of financial reports of village funds accurately and on time. The population in this study was all villages totaling 8 villages in Gianyar Regency who received village funds. The sample is determined by the saturated or census sample method. The data analysis technique uses Smart-PLS 3.0. The results showed that: user involvement had a positive and significant effect on the performance of the SISKEUDES; the education and training program has a negative and not significant effect on the performance of the SISKEUDES; top management support has a negative and significant effect on the performance of the SISKEUDES.